Local cure with apitherapy in a patient with anthrax - Sorelis Beatriz Torres Puente; Sahily Quintero Salcedo; María Despaigne Despaigne (Centro Provincial de Información de Ciencias Médicas, 2016)
The case report of a 67 years patient who was admitted in the Dermatology Service of  "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital  with diagnosis of anthrax in  postero-superior region of the thorax is described. A necrectomy and simple x-ray of thorax are carried out that which show a significant  left pleural effusion; therefore, he was transferred to the Pneumology Service where he is diagnosed with lung neoplasia. The skin infection was treated with antimicrobials of parenteral use and local cures with honey, thus, the total resolution of the lesion was achieved.